EVALUATION OF THE ANTICOAGULANT ACTIVITY OF MARGINS FROM OLIVES EXTRACTION IN THE KHENCHELA REGION - K, . Kadi*1,2; R., . Mrah2, 2; s, Boukeria4; Z., Gueboudji2; I., Hafsaoui2 (university of eloued جامعة الوادي, 2020)
The objective of this study is the evaluation of the anticoagulant activity of polyphenols obtained from olive extracts (Olea europaea L.) Of the margines of two varieties cultivated at Khenchela (East of Algeria) , the first one is souidi from Chacher and the second one is chemlal from Baghai. The physicochemical characteristics of the two varieties studied showed a difference in water content, total solid content (dry matter), total solid in suspension, potential hydrogen, and especially its content in polyphenols and flavonoids. The quantitative analysis of the two extracts has revealed a great richness of the margines of the souidi variety of polyphenols and flavonoids content compared to the margines of the chemlal variety. The dosage of polyphenols is 0.8 mg EAG / mlE) for Souidi and (0.5 mgEAG / mlE) for Chemlal. The in vitro evaluation of the anticoagulant activity of the margines of two varieties souidi and chemlal revealed that the margines of the souidi variety has a good anticoagulant activity vis-à-vis the endogenous pathway Time of Céphaline Kaolin (TCK).
artical
Keywords: margines, chemlal and souidi, physicochemical characteristics, dosage, olives, anticoagulant activity.